Chapter 11: Occupational Toxicology (Principles of Medical Toxicology, 2025)
SynopsisAuthorMr. Wilberforce Kasangaki, PG Scholar, Department of Regulatory Affairs, Ramanbhai Patel College of Pharmacy, CHARUSAT, Changa, Gujarat, IndiaAbstractOccupational toxicology addresses workplace chemical exposures that affect millions of workers across diverse industries, requiring specialized approaches to identification, management, and prevention. Workplace exposures occur through inhalation, dermal contact, and ingestion routes, with inhalation predominating in industrial settings where particulates, gases, vapors, and fumes present significant hazards. Industry-specific risks include silica and asbestos in construction, solvents and heavy metals in manufacturing, pesticides in agriculture, and chemotherapeutic agents in healthcare. Protection measures follow a hierarchical approach prioritizing elimination of the hazard, substitution with safer alternatives, engineering controls like ventilation systems, administrative controls including work rotation, and personal protective equipment as the final defense. Biological monitoring assesses internal dose through biomarkers in blood or urine, while environmental monitoring quantifies workplace contaminant levels using various sampling methods. Medical surveillance programs combine periodic examinations, function testing, and exposure records to detect adverse effects before clinically apparent disease develops. Regulatory frameworks establish permissible exposure limits, require hazard communication through standardized systems, mandate monitoring for certain substances, and establish medical removal provisions for workers showing early signs of toxicity. Occupational toxicologists must understand these complex interactions between workplace hazards, individual susceptibility factors, and regulatory requirements to effectively prevent, recognize, and manage work-related toxic exposures.Keywords: Occupational Exposure, Industrial Hygiene, Biomonitoring, Permissible Exposure Limits, Hazard Communication, Respiratory ProtectionVIEW PDF